(untitled) (Boletin Médico de Postgrado, 2020)
Opioids are the most potent drugs used to mitigate the chronotropic and vasoconstrictor effects that occur during laryngoscopy. A cross-sectional descriptive study was conducted in order to evaluate the hemodynamic stability of morphine during anesthetic induction in patients undergoing abdominal surgery in the Hospital Central Universitario Dr. Antonio María Pineda. The sample included 30 patients with an average age of 38 ± 14.63 years predominantly male (56.67%) and ASA II (53.33%). 40% of patients underwent cholecystectomy and 20% umbilicoplasty and 16.67% inguinal hernia repair. During anesthesia induction, 26.7%, 10% and 50% of patients showed an increase in systolic, diastolic and mean blood pressure > 20 mmHg compared to basal values. Five minutes post induction, all patients showed decreased values ​​of systolic and diastolic blood pressure and only 10% of patients showed changes in mean arterial blood pressure. No adverse effects were recorded. These results show that morphine at a dose of 0.1 mg/kg intravenously 30 minutes before induction allows greater comfort for the patient with minimal hemodynamic changes and no adverse effects.